2011
DOI: 10.5754/hge11153
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Decreases Hepatocellular Carcinoma Cell Sensitivity to Cisplatin-Induced Apoptosis

Abstract: DEX can decrease hepatocellular carcinoma cell sensitivity to CIS-induced cell death by preventing cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…GCs have been demonstrated to protect normal tissue which may be good for patients, but the protection of cancer cells may impair the effect of chemotherapy [27]. Thus, it is understandable that the appeal for reevaluating the administration of GCs in the management of solid cancer patients has emerged recently.…”
Section: Discussionmentioning
confidence: 99%
“…GCs have been demonstrated to protect normal tissue which may be good for patients, but the protection of cancer cells may impair the effect of chemotherapy [27]. Thus, it is understandable that the appeal for reevaluating the administration of GCs in the management of solid cancer patients has emerged recently.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Glucocorticoid-dependent death or survival is directly associated with the selective expression of the short or long isoforms of Bcl-X (Bcl-X S or Bcl-X L ), which are pro-and antiapoptotic, respectively. 17 Cells resistant to glucocorticoid-induced apoptosis, such as some cancer cells 19,20 and fibroblasts, 21 show increased production of Bcl-X L . In the hippocampus, where they induce cell death, glucocorticoids increase the ratio of the proapoptotic molecule Bax relative to the antiapoptotic molecule Bcl-X L .…”
Section: Discussionmentioning
confidence: 99%
“…However, dexamethasone was found to inhibit apoptosis in TGF-beta treated rat hepatoma cells, also likely by increasing Bcl-xL expression in these cells [115]. Several other studies have shown glucocorticoids to be protective in hepatoma carcinoma cells against other apoptotic stimuli [116,117]. Glucocorticoid treatment may also be particularly detrimental in breast cancer.…”
Section: Anti-apoptotic Effects Of Glucocorticoid Signalingmentioning
confidence: 99%